Cold Preservation of Human Adult Hepatocytes for Liver Cell Therapy. Issue 12 (December 2015) - Duret, Cedric; Moreno, Daniel; Balasiddaiah, Anangi; Roux, Solene; Briolotti, Phillipe; Raulet, Edith; Herrero, Astrid; Ramet, Helene; Biron-Andreani, Christine; Gerbal-Chaloin, Sabine; Ramos, Jeanne; Navarro, Francis; et al.
Hepatocyte transplantation is a promising alternative therapy for the treatment of hepatic failure, hepatocellular deficiency, and genetic metabolic disorders. Hypothermic preservation of isolated human hepatocytes is potentially a simple and convenient strategy to provide on-demand hepatocytes in sufficient quantity and of the quality required for biotherapy. In this study, first we assessed how cold storage in three clinically safe preservative solutions (UW, HTS-FRS, and IGL-1) affects the viability and in vitro functionality of human hepatocytes. Then we evaluated whether such cold-preserved human hepatocytes could engraft and repopulate damaged livers in a mouse model of liver failure. Human hepatocytes showed comparable viabilities after cold preservation in the three solutions. The ability of fresh and cold-stored hepatocytes to attach to a collagen substratum and to synthesize and secrete albumin, coagulation factor VII, and urea in the medium after 3 days in culture was also equally preserved. Cold-stored hepatocytes were then transplanted in the spleen of immunodeficient mice previously infected with adenoviruses containing a thymidine kinase construct and treated with a single dose of ganciclovir to induce liver injury. Engraftment and liver repopulation were monitored over time by measuring the blood level of human albumin and by assessing the expression of specific human hepatic mRNAs and proteins in the recipient livers by RT-PCR and immunohistochemistry, respectively. Our findings show that cold-stored human hepatocytes in IGL-1 and HTS-FRS preservative solutions can survive, engraft, and proliferate in a damaged mouse liver. These results demonstrate the usefulness of human hepatocyte hypothermic preservation for cell transplantation.